An Experimental Study of the Core Location and Shape Effect on Seepage and Stability of Zoned Earth Fill Dam - Wissam A. Kidder; Shamil A. Behaya (Tikrit Journal of Engineering Sciences)
Seepage is the main problem of earth dams; most failures occur due to excessive amounts of seepage. In zoned earth dams, clay core minimizes seepage quantity, and its dimensions and shape influence seepage quantity. The shape and location of the core impact on the seepage were investigated in this paper, as sand, a percentage of bentonite clay, and gravel were used to build the physical model inside the hydraulic conductivity device to calculate the amount of seepage through the dam body and to specify the seepage phreatic line. Four core shapes were considered: rectangular, wedge-shaped, forward inclined, and backward inclined with (25%) percent amounts of bentonite clay and various core dimensions and lateral inclinations. A numerical model is adopted using the Geo Studio program to simulate the experimental models and compare results, which showed high agreement in results with (r2=99.4%) correlation factor. The results showed that the trapezoidal core shape was the most effective in reducing drainage, as it reduced drainage by about (62% - 79%) compared with the rectangular core shape at various core side slopes. In addition, the inverse proportions for the core crest to dam crest width ratio affected seepage discharge for all core shapes. There was a direct proportion for the core side slope effect for the trapezoidal core shape and an inverse proportion for the forward and backward-inclined core shapes.